Silage making: Method of fodder conservation and entrepreneurship development: A success story - Jadoun, Y S; Singh, Jaswinder (Indian Farming, 2022)
Amarjit Singh has become a prominent example in the operational area who has adopted this silage making intervention to such a greater extent in the operational area. Many farmers from same as well as from nearby villages got motivated after seeing his results on advantages of silage and started making silage as a routine feeding purpose for their animals. Today, about 60–70% of the farmers in the operational area of the project are making silage at their homes by taking trainings and expert advice from FFP Project team members regarding making good quality of silage and also guidance provided by Amarjit Singh, who keeps on pushing farmers to adopt this intervention as lucrative entrepreneurial venture. He also solves queries of other farmers regarding this technology through the use of social media like WhatsApp, Facebook, phone calls etc. He also motivates unemployed youth, small, marginal and landless farmers to prepare silage as an enterprise in their area for their livelihood concerns.